Canada's Carbon Price Floor - Parry, Ian (IMF Working Papers; Working Paper, 2018)
The pan-Canadian approach to carbon pricing, announced in October 2016, ensures that carbon pricing applies throughout Canada in 2018, with increasing stringency over time to reduce emissions. Canadian provinces and territories have the flexibility to either implement an explicit price-based system-with a minimum price of CAN USD 10 per tonne of carbon dioxide equivalent in 2018, increasing to CAN USD 50 per tonne by 2022-or an equivalently scaled emissions trading system. This paper discusses the rationale for, and design of, the price floor requirement; its (provincial-level) environmental, fiscal, and economic welfare impacts; monitoring issues; and (national-level) incidence. The general conclusion is that the welfare costs and implementation issues are manageable, and pricing provides significant new revenues. A challenge is that the floor price by itself appears well short of what will be needed by 2030 for Canada's Paris Agreement pledge.